Interactive Multimedia Design In Museum Gallery - Zhen, Ling Katharine Ting; Yan, Peng Lim; Amir Sharji, Elyna (2016)
The rapid development of digital technologies has made digital media widely available to everyone. Some museum galleries in Malaysia, such as the National Museum, have made use of interactive multimedia, which provides interaction between the users and the items being displayed. Regardless of the presence and accessibility of interactive multimedia, few studies have indicated that research on museum visitors in Malaysia, especially museums with interactive multimedia display, are still lacking. In this research, an interactive multimedia is proposed to enhance visitors’ experience by using design elements and design principles. With the usage of the Norman’s Emotional Design Model as the conceptual theory, the study was conducted to gain insights of interactive multimedia usage and visitors’ perceptions and preferences. The outcome of this study will provide designers and developers the option of considering work closely in order to deliver the best interface design for interactive multimedia. This research will also benefit the museums in Malaysia as it is able to provide an insight into the awareness of interactive multimedia and touch screens usage for more engaging experience. It also encourages visitors to educate and entertain themselves with interactive and multi-sensory contents. Overall, the results provide directions for curatorial and design criteria issues for interactive multimedia in informal learning institution such as galleries in museums. The results of the research provided suggestion for the use of Norman’s Emotional Design Model, design elements and design principles when developing interactive multimedia in order to enhance user experience in museum gallery